Reactive oxygen species production in the early and later stage of chronic ventilatory hypoxia - Hodyc, Daniel; Johnson, E; Skoumalová, Alice; Tkaczyk, Jakub; Maxová, Hana; Vízek, Martin; Herget, Jan (Physiological research, 2012)
Pulmonary hypertension resulting from chronic hypoxia is at least partly caused by the increased production of reactive oxygen species (ROS). The goal of the presented study was to investigate the dynamics and the site of production of ROS during chronic hypoxia. In our study Wistar rats were kept for 1, 4 and 21 days in an isobaric hypoxic chamber (FiO2=0.1), while controls stayed in normoxia. We compared NO production in expired air, plasma and perfusate drained from isolated rat lungs and measured superoxide concentration in the perfusate. We also detected the presence of superoxide products (hydrogen peroxide and peroxynitrite) and the level of ROS-induced damage expressed as the concentration of lipid peroxydation end products. We found that the production and release of ROS and NO during early phase of chronic hypoxia has specific timing and differs in various compartments, suggesting the crucial role of ROS interaction for development of hypoxic pulmonary hypertension.
Keywords: Pulmonary Artery; zvířata; Hypoxia; Hydrogen Peroxide; Peroxynitrous Acid; Rats; oxid dusnatý; Nitric Oxide; mužské pohlaví; reaktivní formy kyslíku; arteria pulmonalis; hypoxie; plicní hypertenze; krysa rodu Rattus; Rats, Wistar; Animals; Male; Reactive Oxygen Species; kyselina peroxydusitá; potkani Wistar; peroxid vodíku; Hypertension, Pulmonary